2011
DOI: 10.1167/iovs.11-7485
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Experimental Autoimmune Uveoretinitis by Aldose Reductase Inhibition in Lewis Rats

Abstract: These results suggest that AR could be a novel mediator of bovine IRBP-induced uveitis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
0
9
0
6
Order By: Relevance
“…For histopathologic evaluation, the iris-ciliary body complex, anterior chamber, vitreous, and retina were observed under a light microscope. Based on the number and extent of lesions seen in the HE-staining section, histological scores were provided on a scale of 0 to 4 using criteria described previously [ 17 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…For histopathologic evaluation, the iris-ciliary body complex, anterior chamber, vitreous, and retina were observed under a light microscope. Based on the number and extent of lesions seen in the HE-staining section, histological scores were provided on a scale of 0 to 4 using criteria described previously [ 17 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since these drugs have already passed in the Food and Drug Administration (FDA)'s phase I and II clinical trials and have been found to be safe without any major irreversible side effects, and it is expected that ARI such as fidarestat could be developed as novel therapy for preventing ocular inflammation especially uveitis in a relatively shorter time. [92][93][94]…”
Section: Future Directionsmentioning
confidence: 99%
“…Uveitis, the inflammation of the uvea in the eye, is among the leading causes of blindness and vision loss in the world [ 1 4 ]. This disease affects people of all ages, gender, and race, though sex preponderance can be observed in some cases [ 3 , 4 ]. It also affects the working population between 20 and 59 years [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pathology is characterized by elevated levels of proinflammatory cytokines in ocular tissue, which involve the production of inflammatory molecules and reactive oxygen species (ROS) [ 7 ]. The experimental animal model closest to human uveitis is the acute form of bacterial endotoxin, lipopolysaccharide- (LPS-) induced uveitis (EIU) [ 3 , 4 , 8 ]. LPS increases the systemic expression of several inflammatory molecules such as TNF- α , IL-6, MIF, IFN- γ , and MCP-1 and the production of nitric oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation